Pengaruh Orientasi Sudut Anyam Lamina Pada Fiberglass Terhadap Kekuatan Tarik Komposit Matriks Polyester - Risal, Risal; Sudarsono, Sudarsono; Kadir, Abd. (Teknik Mesin Universitas Halu Oleo, 2020)
The purpose of this research is to find the tensile strength of fiberglass composite against the orientation of the lamina weaving angle. In this research composite making uses a hand lay-up method, with a fiber-matrix fraction of 30 % : 70 %. Specimen were made with ASTM D 638-01 tensile test standar. The result showed that the highes tensile test specimen value with the orientation of the weaving lamina angel is 0o/90o, 0o/90o, 0o/90o, 0o/90o, 0o/90o, 0o/90o, 0o/90o, 0o/90o which is 135,568 N/mm2. While the lowest tensile test specimen value are in the orientation of the weaving angles of lamina 0o/90o, 15o/105o, 30o/120o, -15o/-105o, -15o/-105o, 30o/120o, 15o/105o, 0o/90o, with voltage values tensile strength of 106,447 N/mm2. Keywors: Composite, fiberglass, angle orientation, tensile trength.